Towards highly active and stable nickel-based metal-organic frameworks as ethylene oligomerization catalysts - Arrozi, Ubed S. F.; Bon, Volodymyr; Kutzscher, Christel; Senkovska, Irena; Kaskel, Stefan (Dalton Transactions, 2019)
Catalytic ethylene oligomerization proceeds under mild conditions with high activity using porous or non-porous nickel-based coordination polymers/metal-organic frameworks (MOFs) as catalysts. The role of MOFs as catalyst precursors and the crucial impact of metal coordination on the catalyst activity and leaching are elucidated by comparing MOFs constructed from different clusters and linkers. The stronger the coordination bond of organic linkers to the Ni center, the lower the catalytic activity of the MOF, as shown for CPO-27(Ni). The highest activity and stability were obtained with the [Ni 3 (ndc) 3 (DMF) 2 ((CH 3 ) 2 NH) 2 ] n catalyst.
CRIS-Team Scopus Importer:2022-04-14